Faktor-Faktor yang Berhubungan dengan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) pada Balita Di Daerah Pesisir Kota Sibolga Tahun 2020 - Pasaribu, Rita Kristina; Santosa, Heru; Kumala, Shirly; Nurmaini, Nurmaini; Hasan, Delina (Ridwan Institute, 2021)
ISPA (Acute Respiratory Tract Infection) is a transmitted respiratory tract disease caused by environmental and human factors. Balita (below five year-old children) is very vulnerable to it. It was caused by virus or bacteria. The symptoms are high fever, followed by pain in throat, difficult to swallow, flu, and coughing with or without phlegm transmitted through patients' droplet (Riskesdas,2018). Revealed that, nationally, the prevalence of ISPA in balita was 12.8%, 8. 7% in North Sumatera, and 57% in Sibolga. The objective of the research was to analyze some factors which were correlated with the incidence of ISPA in balita at the coastal area of Sibolga . The data were gathered by using questionnaires. The research used cross sectional design. The samples were 265 (Isaac and Michael tables). The data were analyzed by using univariate analysis, bivariate analysis, and multivariate analysis with multiple logistic regression tests. From the samples, it was found that 144 of them (54.3%) were affected by ISPA and 121 of them (45. 7%) were not. The result of univariate analysis showed that 141 respondents (53.2%) had good requirement for their floors, 146 of them (55.1%) for walls, 70 of them (26.4%) for air ventilation, 257 of them (97%) for room temperature, 225 of them (84.9%) for lighting, 233 of them (87.9%) for moisture, 181 of them (68. 3%) for population density. From the factor of children, it was found that there were 131 boys (49.4%), 188 of the balita (70.9%) were 6- 35 months old, 217 of them (81.9%) were not BBLR, 206 of them (77.7%) had bad nutrition, 160 of them (60.4%) got vitamin A, 139 of them (52.5%) got immunization completion, 177 of them (66.8%) were breastfed with ASI (breast milk), 202 of them (76. 2%) smoked, 40 of them (15.1 %) used wood as fuel, and 27 of them (10.2%) used mosquito coils The result of bivariate analysis showed that 8 (eight) independent variables which were correlated were smoking (p-value=0. 003), using mosquito coils (p-value=0.026), floors (p-value=0.033), walls (p-value=0.002), population density (p-value=0.001), nutritional status (pvalue=0.001), air ventilation (p-value=0.012), Vitamin A(p-value=0.024), and complete immunization (p-value=0.035). The result of multivariate analysis showed that the variables of smoking, condition of house walls, nutritional status, and immunization completion caused the incidence of ISPA in balita at the coastal area of Sibolga (75.8%). It is recommended that prevent ISPA by increasing nutritional status, ASI, visiting posyandu, and no smoking inside their houses.